Proceedings of the Ninth International Conference on Tangible, Embedded, and Embodied Interaction 2015
DOI: 10.1145/2677199.2680596
|View full text |Cite
|
Sign up to set email alerts
|

DisplaySkin

Abstract: Mobile devices can provide people with contextual information. This information may benefit a primary activity, assuming it is easily accessible. In this paper, we present DisplaySkin, a pose-aware device with a flexible display circling the wrist. DisplaySkin creates a kinematic model of a user's arm and uses it to place information in view, independent of body pose. In doing so, DisplaySkin aims to minimize the cost of accessing information without being intrusive. We evaluated our pose-aware display with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In a conventional wristwatch-type device, the display area is limited and fixed, namely the watch face. Flexible and curved display devices [30,33] expand display area from a portion on the wrist to whole circumference of the forearm [6,39,42]. Snaplet [39] is a sensoraugmented flexible display device that can detect the shape of the display, e.g., convex and flat, and offers different interactions depending on the shape.…”
Section: Interaction On the Arm And Handmentioning
confidence: 99%
See 4 more Smart Citations
“…In a conventional wristwatch-type device, the display area is limited and fixed, namely the watch face. Flexible and curved display devices [30,33] expand display area from a portion on the wrist to whole circumference of the forearm [6,39,42]. Snaplet [39] is a sensoraugmented flexible display device that can detect the shape of the display, e.g., convex and flat, and offers different interactions depending on the shape.…”
Section: Interaction On the Arm And Handmentioning
confidence: 99%
“…SleeD [42] is a touch-sensitive sleeve display that facilitates explicit interaction with a wall-type display. DisplaySkin [6] is a whole-wrist circumference display that is flexible [30], and aims at realize implicit interactions with the user by adjusting the position and the orientation of displayed information to the forearm posture relative to the shoulder. An experiment showed that the proposed pose-aware display reduced the time to acknowledge the notification, and minimized the overall interruption.…”
Section: Interaction On the Arm And Handmentioning
confidence: 99%
See 3 more Smart Citations